Characterization of cultivated pumpkin (Cucurbita moschata Duchesne) landraces for genotypic variance, heritability and agro-morphological traits - EZIN, VINCENT; Gbemenou, Ulrich Herbert; Ahanchede, Adan (My University, 2022)
Cucurbita moschata (Pumpkin) is a multipurpose species whose fruits and sometimes oil seeds are used for various purposes. It is low in calories and is a significant source of income. Despite the great potential of the pumpkin production and usage, there is no attention to establish the varieties grown in Benin for proper documentation. Therefore, the present study was carried out to (i) evaluate the agromorphological variability of pumpkin accessions collected in Benin and (ii) investigate heritability, genetic gain, phenotypic and genotypic variances of the agronomic traits. Six landraces from one hundred and twenty accessions collected in Benin were sown and characterized. The agronomic experiment was laid out in a complete randomized block design with three replicates. Out of the twenty-seven quantitative descriptors measured, fifteen were found to be significant. The 50% emergence time (p = 0.03), the number of female flowers (p = 0.02), the seed width (p = 0.05) and the ratio seed width and length (p = 0.01) were significant. A highly significant difference was observed with the days to 50% flowering and the length of male flower stalks (p = 0.002), the average weight of one hundred seeds (p = 0.009). Fruit set at 50%, length of female flower peduncle, number of male flowers, mean fruit weight, fruit length, fruit diameter, average number of seeds per fruit and seed length were very highly significant (p < 0.001). Fruit color and shape, seed color and leaf color showed phenotypic variability. A positive correlation (r = 0.76; p < 0.05) was observed between average fruit weight and average number of seeds per fruit. Principal component analysis and Hierarchical Ascending Classification revealed three classes. Estimates of the phenotypic coefficient of variation were higher than estimates of the genotypic coefficient of variation for most characters. High heritability was observed for fruit diameter (96.73%), average fruit weight (96.46%) and fruit length (94.64%). High heritability associated with high genetic advance was observed for these traits. In sum, the genetic diversity observed within the landraces of pumpkin shows that there is possibility for further selection.
Keywords: Cucurbita moschata; Fruit shape; Diversity; Heritability; Genetic advance